Novel Anaplasma Variants in Small Ruminants From Central China - Zhang, Yan; Cui, Yanyan; Sun, Yanting; Jing, Huiyuan; Ning, Changshen (Frontiers in Veterinary Science, 2020)
Anaplasma capra is an emerging zoonotic pathogen that pose a risk to human and animal health. Numerous variants in a variety of domestic and wild animals had been reported since its discovery and confirmation in humans in 2015 and its first detection from goat blood during 2012-2013. In order to find out more A. capra variants data of A. capra in central China, 16S rRNA, gltA, groEL and msp4 genes of this pathogen were amplified from sheep and goat samples collected during 2011-2015 and phylogenetic analysis of these sequences were conducted. The results of 16S rRNA and gltA manifested that partial sequences obtained in this study were 100% identical with A. capra isolates, while phylogenetic analysis results of groEL and msp4 showed that the obtained sequences were independent with all other Anaplasmas, formed separate branches on the evolutionary trees. What needed to be emphasized was that the 16S rRNA and gltA gene sequences of X51(KX505302 and KX450269), a sample from Shandong in 2011, were found to be 100% identical with A. capra. Therefore, we could speculate that the occurrence of A. capra may be earlier than its first discovery and report. And the A. capra isolates in central China were novel variants which were different from known genotypes.